Intraoperative identification of major blood supply to Adamkiewicz artery after multistep surgeries in thoraco-abdominal aortic aneurysm repair. (23rd January 2020) - Sakatsume, Ko; Kawatsu, Satoshi; Adachi, Osamu; Saiki, Yoshikatsu
Abstract: Herein, we report a case of thoraco-abdominal aortic repair in a 55-year-old man with a multiple treatment history for aortic aneurysm and aortic dissection. A computed tomography scan revealed that the Adamkiewicz artery was connected to an occluded intercostal artery, suggesting that the left inferior epigastric artery was the key artery supplying the Adamkiewicz artery; the key artery was identified through direct monitoring of cerebrospinal fluid temperature and selective hypothermic perfusion. No spinal cord injury was detected during the postoperative period.